Implementation of EOQ and ROP inventory control for raw materials in book printing businesses - Heppy Putri Agustin; Endra Rahmawati; Pradita Maulidya Effendi (TEKNOSAINS : Jurnal Sains, Teknologi dan Informatika, 2026)
Book publishing businesses often face challenges in managing raw materials due to the diverse specifications of books. In reality, manual stock control can lead to inaccurate inventory data. This can lead to excess or shortages of stock and increased storage costs, disrupting the production process. This study aims to develop a web-based application for raw material inventory control in book printing by integrating the Economic Order Quantity (EOQ) and Reorder Point (ROP) methods. The application calculates the optimal order quantity using the EOQ method to minimize total inventory costs, while the ROP method determines the appropriate reorder point to prevent delays in material replenishment. The results indicate that the integration of EOQ and ROP provides effective recommendations for optimal ordering and timely replenishment, thereby improving stock stability. Black-box testing across 64 scenarios confirmed that all system functions operated correctly, while User Acceptance Testing (UAT) showed an acceptance rate of 84%, indicating good user satisfaction. Overall, the web-based inventory control system with the EOQ and ROP methods is able to optimize the determination of order quantities and ensure that raw material replenishment can be carried out on time